1993
DOI: 10.2135/cropsci1993.0011183x003300040012x
|View full text |Cite
|
Sign up to set email alerts
|

F2 Hybrids of Host Plant Germplasm and Cotton Cultivars: I. Heterosis and Combining Ability for Lint Yield and Yield Components

Abstract: Although pest‐resistant cotton (Gossypium hirsutum L.) germplasm is available, it is generally not equal to adapted cultivars and other elite germplasm in yield. Cotton F2 hybrids could provide a means to combine beneficial traits of high‐yielding adapted cultivar (elite) germplasm with those of pest‐resistant germplasms. In the F2 heterosis and combining ability were studied for lint yield and the primary yield component boll number as well as for the secondary yield components of lint percentage and boll wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
37
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 0 publications
6
37
0
Order By: Relevance
“…Parents with dominant genes were responsible for increased lint % in both generations. The present results are also in line with the findings of Tang et al (1993), McCarty et al (1996McCarty et al ( , 2004a, Hussain et al (1999), Ahmad et al (2003b), Yuan et al (2005), Aguiar et al (2007) and Ali and Awan (2009), who reported additive type of gene action with partial dominance for inheritance of lint%. However, Tang et al (1996), Godoy and Palomo (1999), Basal and Turgut (2005), Iqbal et al (2005), Mei et al (2006), Esmail (2007 and Gamal et al (2009) concluded non-additive type of gene action with over-dominance for lint %.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Parents with dominant genes were responsible for increased lint % in both generations. The present results are also in line with the findings of Tang et al (1993), McCarty et al (1996McCarty et al ( , 2004a, Hussain et al (1999), Ahmad et al (2003b), Yuan et al (2005), Aguiar et al (2007) and Ali and Awan (2009), who reported additive type of gene action with partial dominance for inheritance of lint%. However, Tang et al (1996), Godoy and Palomo (1999), Basal and Turgut (2005), Iqbal et al (2005), Mei et al (2006), Esmail (2007 and Gamal et al (2009) concluded non-additive type of gene action with over-dominance for lint %.…”
Section: Discussionsupporting
confidence: 92%
“…These results confirm the findings of Iqbal et al (2005) who reported overdominance type of gene action for seed cotton yield. However, Tang et al (1993), McCarty et al (1996), Ahmad et al (1997), Godoy and Palomo (1999), Hussain et al (1999), Khan (2003), Lukonge (2005), Wu et al (2006), Aguiar et al (2007), Lukonge et al (2007) and Khan et al (2007) reported additive type of genetic control for seed cotton yield. The discrepancies with respect of phenotypic manifestation of this complex parameter might be due to different cultivars used under different environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Baloch et al (1995) revealed the importance of specific combining ability for yield, 100-seed weight and lint percentage, and general combining ability for boll number per plant and lint percentage. Wilson (1991) : Tang et al(1993) and Nadeem et al (1998) reported significant general and specific combining ability effects for lint yield, lint percentage, seed cotton weight per boll and boll number per plant.…”
mentioning
confidence: 99%
“…Previous findings are also of view about the F 2 hybrids heterosis in cotton [7]. On the other hand, a group of physical properties can play a vital role in determination of textile use and economic value of cotton.…”
Section: Introductionmentioning
confidence: 85%